Influence of method of processing supplemental alfalfa on intake and utilization of dormant, bluestem-range forage by beef steers - Lintzenich, B.A.; Cochran, R.C.; Vanzant, E.S.; Beaty, J.L.; Brandt, Robert T., Jr.; Nagaraja, Tiruvoor G.; St. Jean, G. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
A digestion trial was conducted to determine the effect of method of processing supplemental alfalfa on the intake and utilization of dormant, bluestem-range forage. Supplement treatments were 1) control: no supplement; 2) ground and pelleted, suncured alfalfa; 3) ground and pelleted dehydrated alfalfa; and 4) longstem alfalfa hay. Bluestem forage intake (% BW), diet digestibility, and ruminal dry matter fill 4 hours after feeding were increased (P<.10) when supplemental alfalfa was fed, compared with no supplementation. Little difference was evident among different forms of supplemental alfalfa for most of the forage utilization characteristics measured. However, a weak trend (P=.18) was observed for increased intake of bluestem forage by the steers supplemented with dehydrated alfalfa pellets compared with suncured alfalfa pellets.
Keywords: Beef; Supplements; Intake; Crude protein flow; Dormant range; Alfalfa